Cultivation of black truffle to promote reforestation and land-use stability - Bonet, J. A.; Fischer, C. R.; Colinas, C. (Agron. Sustain. Dev., 2006)
Cultivation of black truffle, Tuber melanosporum Vitt., has become an important agricultural alternative in rural Mediterranean regions due to its success in relatively harsh conditions, its high market value and diminishing production in natural areas. In addition, truffle cultivation requires relatively low agricultural inputs, promotes reforestation and economic restoration of rural lands and land-use stability. However, there remain major issues regarding the management practices to ensure successful black truffle production. We therefore conducted an experiment to evaluate 3 levels of irrigation based on monthly water deficit and the effects of currently applied weed control systems and fertilization. Treatment effects were evaluated by examining the mycorrhizal status of out-planted 1-yr-old Quercus ilex L. seedlings and seedling growth parameters after 18 months in 3 distinct experimental truffle plantations located in the foothills of the Spanish Pyrenees. We found that replacing one-half of the water deficit of the driest month (moderate irrigation) promoted the proliferation of T. melanosporum mycorrhizae, while high irrigation reduced fine root production and truffle mycorrhizae. Glyphosate weed control improved seedling survival by up to 16% over control seedlings without jeopardizing truffle mycorrhizae in the first year. Fertilization did not improve seedling growth or influence its mycorrhizal status. We describe the persistent relationship between this ectomycorrhizal fungus and Q. ilex by quantifying old and new mycorrhizae and we discuss the ecological implications of the symbiosis
Keywords: agricultural alternative; ectomycorrhiza; Quercus ilex; water deficit